Evaluasi Pembelajaran Pjok pada Siswa Kelas XI SMK Roudhlotul Mubtadiin Balekambang (Universitas Negeri Semarang, 2023)
The purpose of this study is to find out and describe the evaluation of the process of implementing PJOK learning in class XI students of SMK Roudhlotul Mubtadiin Balekambang in 2021. The results show that teacher learning planning activities do not plan well, only stop at the syllabus, lesson plans and teaching materials. Learning implementation activities are still focused on teachers, learning has not led to analytical activities according to basic competencies. In the evaluation activities the teacher does not compile an assessment instrument, the teacher's assessment is carried out in a modest manner without being guided by the assessment instrument. The conclusion of the research is that the evaluation of the learning implementation process has not run optimally. Starting from the planning, implementation and evaluation of learning activities, it has not been carried out properly